Some New Separation Axioms with Application in Dimension Theory - Kadhim Jebur, Sema (Al-Qadisiyah Journal of Pure Science, 2018)
"The aim of this paper is to introduce and study" the notions "of regular and normal topological spaces" and give some applications in dimension theory.